2004
DOI: 10.1093/humrep/deh274
|View full text |Cite
|
Sign up to set email alerts
|

Disparate effects of relaxin and TGF 1: relaxin increases, but TGF 1 inhibits, the relaxin receptor and the production of IGFBP-1 in human endometrial stromal/decidual cells

Abstract: The present study showed that in undifferentiated endometrial stromal cells, progestin increases the RLX receptor content to enhance the effect of RLX on the target gene (IGFBP-1). In decidual cells, RLX alone up-regulates its receptor, resulting in a large scale induction of IGFBP-1. TGFbeta1 has an inhibitory effect on LGR7 and IGFBP-1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
40
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 23 publications
7
40
0
Order By: Relevance
“…We found that RXFP1 expression was reduced in IPF fibroblasts and that expression was reduced even further in the presence of TGF-b. These data support previous observations that TGF-b is associated with reduced expression of RXFP1 (30). In our hands, supraphysiologic in vitro concentrations of TGF-b were observed to decrease RXFP1 in IPF fibroblasts.…”
Section: Discussionsupporting
confidence: 93%
“…We found that RXFP1 expression was reduced in IPF fibroblasts and that expression was reduced even further in the presence of TGF-b. These data support previous observations that TGF-b is associated with reduced expression of RXFP1 (30). In our hands, supraphysiologic in vitro concentrations of TGF-b were observed to decrease RXFP1 in IPF fibroblasts.…”
Section: Discussionsupporting
confidence: 93%
“…This occurred constitutively and was significantly increased in the presence of ligand. Relaxin treatment of human endometrial (52) and decidual cells (23) increases RXFP1 mRNA, but the data presented here suggest that relaxin action in the fetal membranes is also controlled by the level of its receptors expressed on the cell surface of its target cells.…”
Section: Discussionmentioning
confidence: 55%
“…In mouse, RXFP2 mRNA is present in testis and gubernaculum (Overbeek et al, 2001). In human, RXFP2 mRNA is found in uterus and testis Mazella et al, 2004). By immunohistochemistry, RXFP2 epitopes have been identified in spermatocytes, spermatids, and Leydig cells within the human testis, and in the epididymal epithelium (R. Ivell, unpublished data).…”
Section: Table 3 Agonists and Antagonists At Receptors For Relaxin Anmentioning
confidence: 99%
“…Rats treated with monoclonal relaxin antibody during the second half of pregnancy display a lack of nipple devel- ; e mRNA by RT-PCR ; f mRNA by RT-PCR (Kubota et al, 2002); g mRNA by RT-PCR (Samuel et al, 2003b); h mRNA by RT-PCR, protein by immunohistochemical analysis (Luna et al, 2004); i mRNA by RT-PCR (Samuel et al, 2004a); j mRNA by RT-PCR (Mazella et al, 2004); k mRNA by RT-PCR (Overbeek et al, 2001); l mRNA by Northern blot analysis ; m mRNA by RT-PCR (Nguyen et al, 2003); n mRNA by RT-PCR (Siebel et al, 2003); o mRNA by RT-PCR (Samuel et al, 2003b); p mRNA by RT-PCR (Hombach- Klonisch et al, 2003); q mRNA by Northern blot analysis and in situ hybridization (Kawamura et al, 2004); r mRNA by RT-PCR (Liu et al, 2003b); s mRNA by RT-PCR (Liu et al, 2003a); t protein by receptor autoradiography (Osheroff et al, 1990); u protein by receptor autoradiography ; v protein by immunohistochemistry ; w protein by receptor autoradiography ;…”
Section: Table 3 Agonists and Antagonists At Receptors For Relaxin Anmentioning
confidence: 99%